1996
DOI: 10.1111/j.1745-9125.1996.tb01195.x
|View full text |Cite
|
Sign up to set email alerts
|

More on Demeanor and Arrest in Dade County*

Abstract: A recent study of police behavior using data collected in Dade County, Florida, found that citizen demeanor is a spurious correlate of arrest in light of control for criminal conduct (Klinger, 1994). This finding calls into question the long‐standing belief that hostility directly increases the odds of arrest in police‐citizen encounters. Responding to this research, Lundman (1994) reanalyzed data used in several previous studies that had reported hostility effects. His reanalysis offered limited support for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 23 publications
4
76
0
Order By: Relevance
“…Vignettes characterized offenders as either calm or hostile. This strategy was consistent with Klinger's (1996) operational definition of demeanor. Other aspects of vignettes were held constant: the victim and offenders were married, the incident took place at home, and the victim accused the offender of physically pushing her into the wall.…”
Section: Independent Variablessupporting
confidence: 76%
See 1 more Smart Citation
“…Vignettes characterized offenders as either calm or hostile. This strategy was consistent with Klinger's (1996) operational definition of demeanor. Other aspects of vignettes were held constant: the victim and offenders were married, the incident took place at home, and the victim accused the offender of physically pushing her into the wall.…”
Section: Independent Variablessupporting
confidence: 76%
“…Oppenlander stated that officers charge an offender with an offense that serves as "retribution for the assailant's hostility to the police" (p. 457), such as public intoxication or resisting an officer. Klinger (1996) examined the relationship between an offender's demeanor and the arrest decision. He found that only those cases in which the offender was extremely hostile (e.g., raising a middle finger or open verbal disrespect) were significantly related to the arrest decision.…”
Section: Situational Factorsmentioning
confidence: 99%
“…In addition to the potentially deleterious effects that such disrespectful treatment of citizens may have on police legitimacy, this kind of behavior also increases the likelihood that police-citizen encounters will be rife with animosity emanating from both parties. Prior research shows that citizen demeanor can influence police actions and, therefore, help determine whether an encounter is civil or confrontational (Engel et al, 2000;Klinger, 1996;Lundman, 1996;Worden & Shepard, 1996). This finding indicates that people, such as the young men under study here, who are subjected to routine maltreatment at the hands of police may begin approaching police encounters with an uncooperative demeanor.…”
Section: Discussionmentioning
confidence: 69%
“…The likelihood of these extralegal factors seeping into criminal justice agents' decision-making is greatest when legal factors (e.g., offense seriousness, evidence of criminal activity) are murkiest (Kalven & Zeisel, 1966;Reskin & Visher, 1986;Spohn & Cederblom, 1991). An abundant body of knowledge has established that police decisions can be affected by a suspect's race and/or social standing (Alpert, Dunham, & MacDonald, 2004;Mastrofski, Reisig, & McCluskey, 2002;Skogan, 2005), gender (Brunson & Miller, 2006a), demeanor (Engel, Sobol, & Worden, 2000;Klinger, 1996;Lundman, 1996;Worden & Shepard, 1996), and the environment wherein a given police-citizen encounter transpires (Fagan & Davies, 2000;Klinger, 1997;Meehan & Ponder, 2002;Terrill & Reisig, 2003). This gives rise to decision-making that citizens may perceive as arbitrary even when officers have no intention to discriminate and are unaware that they are conveying such an impression.…”
Section: Introductionmentioning
confidence: 99%
“…(I did 12Indeed, the validity of extant findings that extralegal variables--particularly demeanor--exert independent effects on police action is currently a source of considerable controversy in criminology. See Klinger (1994Klinger ( , 1996a, Lundman (1994Lundman ( , 1996a, and Worden and Shepard (1996) for details. 13Researchers inclined to treat each individual in encounters with multiple citizens as a separate unit of analysis (e.g., Mastrofski, et aL, 1995) could use separate FAS scores for each individual.…”
Section: Discussionmentioning
confidence: 99%